"… jene, die ihre hände hilfreich zum bau erheben …": Zur zeitlichen Konkordanz von Weihe und Bauvollendung am Beispiel der Wiener Augustinerkirche und Georgskapelle - Buchinger, Günther; Schön, Doris (RIHA Journal, 2011)
The Augustinian Church in Vienna and the adjacent St. George's Chapel have recently been analysed for the first time according to structural archaeological and art historical criteria and these results compared with the plentiful written sources. The interdisciplinary research was part of the project researching the architectural history of the Vienna Hofburg, which is based at the Art Historical Commission of the Austrian Academy of Sciences, and has resulted in new discoveries, which have necessarily led to a re-assessment of the rarely-challenged older data about the architectural history of the buildings. The associated art historical view of the German roots of the artistic spatial plan behind the Augustinian Church is also for the most part untenable.